Enhancing the efficacy of electrolytic chlorination for ballast water treatment by adding carbon dioxide. Issue 1 (15th June 2015) - Cha, Hyung-Gon; Seo, Min-Ho; Lee, Heon-Young; Lee, Ji-Hyun; Lee, Dong-Sup; Shin, Kyoungsoon; Choi, Keun-Hyung
Highlights: Injection of CO2 into electrochlorination increased plankton mortality compared to electrochlorination only. Total residual oxidant concentration remained higher during the 5-day incubation with CO2 injection. Injection of CO2 into electrochlorination can reduce power consumption. CO2 used for electrochlorination for ballast water treatment could be trapped from ships exhaust fumes. Abstract: We examined the synergistic effects of CO2 injection on electro-chlorination in disinfection of plankton and bacteria in simulated ballast water. Chlorination was performed at dosages of 4 and 6 ppm with and without CO2 injection on electro-chlorination. Testing was performed in both seawater and brackish water quality as defined by IMO G8 guidelines. CO2 injection notably decreased from the control the number of Artemia franciscana, a brine shrimp, surviving during a 5-day post-treatment incubation (1.8 and 2.3 log10 reduction in seawater and brackish water, respectively at 6 ppm TRO + CO2 ) compared with water electro-chlorinated only (1.2 and 1.3 log10 reduction in seawater and brackish water, respectively at 6 ppm TRO). The phytoplankton Tetraselmis suecica, was completely disinfected with no live cell found at >4 ppm TRO with and without CO2 addition. The effects of CO2 addition on heterotrophic bacterial growth was not different from electro-chlorination only. Total residual oxidant concentration (TRO) more rapidly declined in electro-chlorination of both marine and brackish waters compared to chlorine + CO2 treated waters, with significantly higher amount of TRO being left in waters treated with the CO2 addition. Total concentration of trihalomethanes (THMs) and haloacetic acids (HAAs) measured at day 0 in brackish water test were found to be 2- to 3-fold higher in 6 ppm TRO + CO2 -treated water than in 6 ppm TRO treated water. The addition of CO2 to electro-chlorination may improve the efficiency of this sterilizing treatment of ballast water, yet the increased production of some disinfection byproducts needs further study.